Sistem Informasi Administrasi Pada Percetakan Glory Menggunakan Embarcadero XE2 Berbasis Client Server - Johansen; Sri Hartati; Dodi (Universitas Mahakarya Asia, 2022)
The more advanced the development of science and technology, especially in the field of computers, brings major changes by providing various kinds of programs that can facilitate all kinds of human activities. Like the Glory Printing, which is one of the printers in Baturaja, it still uses the manual system to make reports. This causes problems such as missing or scattered notes. Based on these problems, it is necessary to develop an administrative information system that is useful for helping to collect data on the administrative process of selling goods. The process of making information systems using interview methods, observation methods, and library methods. The software design is accompanied by PHPMyAdmin and XAMPP Version 5.6 software, which contains customer data, order data, and payment data. This information system is expected to facilitate transactions and financial reports.